Superconductivity in nanocrystalline tungsten thin films growth by sputtering in a nitrogen-argon mixture - Hofer, J. A.; Haberkorn, N.; Haberkorn, Néstor (Elsevier, 2019)
Fil: Hofer, J. A. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina